Analysis of tautomeric equilibrium in (E)-4,6-dibromo-2-[(4-fluorophenylimino)methyl]-3-methoxyphenol compound - Kastas, Cigdem Albayrak; Kastas, Gokhan; Gur, Mahmut; Muglu, Halit; Büyükgüngör, Orhan (Elsevier BV, 2015)
In this study, the tautomeric equilibrium between the phenol-imine and keto-amine structural forms of (E)-4,6-dibromo-2-[(4-fluorophenylimino)methyl]-3-methoxyphenol compound has been investigated with experimental (XRD, UV-vis and NMR) and theoretical (DFT and TD-DFT) methods. The results clearly show that structural preference of the compound is definitely depended on its state. Namely, the compound exists in phenol-imine form in the solid state while one or both of these forms can be seen in solvent media. For example, the compound prefers phenol-imine form in benzene while both forms exist in EtOH and DMSO solvents. Coexistence of two forms has been quantified with NMR studies, giving a ratio of 11:9 for phenol and keto structures of the compound in acetone-d6 solvent.
Keywords: X-ray; Schiff base; Keto-amine; Phenol-imine; NMR; Tautomerism; 6. Clean water; 3. Good health